JAKARTA ISLAMIC INDEX (JII) PASKA PANDEMI - Catur Kumala Dewi; Danna Solihin; Rina Masithoh Hariyadi; Nurfitriani Nurfitriani; Heriyanto Heriyanto (DEDIKASI : Jurnal Ilmiah Sosial, Hukum, Budaya, 2022)
Jakarta Islamic Index (JII) is one of the Islamic stock indexes consisting of the 30 most liquid Islamic stocks listed on BER. The review of sharia shares is carried out in May and November every year according to the schedule by the OJK. The Jakarta Islamic Index (JII) is one of the Islamic stock indexes consisting of the 30 most liquid Islamic stocks listed on the IDX. The review of sharia shares is carried out in May and November every year according to the schedule by the OJK. January-February 2020 before the pandemic JII's performance fell by 18.4% and 19.1%, respectively, and since the Covid-19 case was first announced in Indonesia, JII increased by 7.8%. JII recorded improved performance during the pandemic even better than before the pandemic. This study uses secondary data, namely by tabulating time series data on the number of shares in the index (sheet) taken from idx. The population of data from JII used Yoy 2022 and 2021 data where 2021 data is a major evaluation with an effective constituent period from August to November 2021 while 2021 data is minor data with an effective constituent period from March to May 2022. 2022 minor data results from the evaluation of the number of shares for the index is calculated based on 15% of the capitalization of each issuer while the 2021 major data from the evaluation of the number of shares for the index is calculated based on 25.5% of the capitalization of each issuer. The capitalization ratio presents data on the number of shares for the 2021 major index to be greater than the number of shares for the 2022 minor index